2014
DOI: 10.1007/s00421-014-2878-x
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity intermittent cycling increases purine loss compared with workload-matched continuous moderate intensity cycling

Abstract: PurposeExercise at 50–60 % of peak oxygen consumption (VO2 peak) stimulates maximal fat oxidation rates. Despite a lower estimated work performed; high-intensity intermittent exercise (HIIE) training produces greater fat mass reductions when compared with workload-matched continuous (CON) steady state exercise. No metabolic basis has been documented nor mechanisms offered to explain this anomaly. This study investigated the physiological and metabolic responses of two different workload-matched exercise protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
4
20
0
2
Order By: Relevance
“…On the other hand, since hypoxanthine indicates ATP energy discharge, it can be considered as an indicator for energy discharge and cellular metabolic stress (18). In this study that showed the significant increase of xanthine and hypoxanthine concentrations, this increase represents the high decomposition of ATP in high-intensity interval activities, and this study is thus consistent with Gerber et al (19,20). Similarly, Zielinski et al in their research studies reported an increase in xanthine and hypoxanthine levels after the activity of these variables.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, since hypoxanthine indicates ATP energy discharge, it can be considered as an indicator for energy discharge and cellular metabolic stress (18). In this study that showed the significant increase of xanthine and hypoxanthine concentrations, this increase represents the high decomposition of ATP in high-intensity interval activities, and this study is thus consistent with Gerber et al (19,20). Similarly, Zielinski et al in their research studies reported an increase in xanthine and hypoxanthine levels after the activity of these variables.…”
Section: Discussionsupporting
confidence: 91%
“…This chemical feature may mean that uric acid helps to control oxidative stress generated by exercise, at the same time reflecting greater ATP flux associated with elevated energy requirements. Purine catabolism increases and the higher concentrations of sub-products of this metabolism are formed [32]. Xanthine oxidoreductase is a key intracellular enzyme of purine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, when changes in substrate oxidation rates in bicycle ergometer at the level of 50% of 90 minute maxVO 2 during continuous and intermittent exercises, it was figured out that there was no significant difference on total energy expenditure; however, in intermittent exercises the fat oxidation rate was lower than continuous exercises (Warren et al, 2009). On the other hand, Gerber et al (2014) stated that more fat loss observed with the high intensity intermittent exercise when compared with continuous steady state exercise.…”
Section: Discussionmentioning
confidence: 99%